Effect of Short Term Antiretroviral Therapy on CD4+ Cells and Immunoglobulins in HIV Sero-positive Subjects (Journal of Biomedical Investigation, 2008)
The study was designed to assess the effect of short-term antiretroviral therapy (ART) on IgA, IgG and IgM and CD4+ T cell counts in HIV seropositive subjects. 20 confirmed HIV seropositive subjects, aged between 15-65 years were recruited for the study. They were on triple combinations therapy consisting zidovudine, lamivudine and nevirapine. 20 HIV seronegative subjects were used as control. Blood sample was collected from the participants for the determination of the above parameters. The CD4+ T cell counts show no significant difference between pre-ART and 2 months post-ART (P>0.05) but was significantly higher by 4 months post-ART compared with the pre-ART (p
Keywords: ART; RVD; human